Interactive Methods – Challenge or Opportunity - Kirilova, Katya; Kazakova, Maria (Research Papers, 2025)
Interactive teaching methods are essential for the educational system in our country and a serious challenge in the learning process. They are closely related to the application of technologies, through which an educational service adequate to its time is provided. The report presents the results of an empirical study on the application of interactive methods in the educational process, their possibilities and main challenges.
Keywords: Teaching; Interactive methods; Education